EFISIENSI TEKNIS PRODUKSI TANAMAN JAHE DI PROVINSI JAWA TIMUR: PENDEKATAN STOCHASTIC FRONTIER ANALYSIS - Muhammad Fahrul Aziz; Budiasih Budiasih (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Ginger is a spice and medicinal plant that much needed by industry and society. However, ginger production decreased and even experienced a trade balance deficit. One solution that can be done is through intensification or efficiency improvement, especially in the largest ginger-producing province in Indonesia, namely East Java Province. The data used is raw data of Cost Structure of Horticultural Cultivation Household Survey (SOUH) 2018. The results of the analysis using Stochastic Frontier Analysis (SFA) show that four factors of production, namely land area, number of workers, amount of seeds used, and amount of fertilizer used, can increase ginger production significantly with a fairly high level of technical efficiency. However, technical inefficiencies are still found which cause ginger production to not be maximized. There are seven from eight variables that have a significant effect, namely farmer age, farmer education level, farmer group participation, pest control, receiving farm assistance, use of credit, and land ownership status. Meanwhile, the variable of farmer gender has no significant effect.